THE DYNAMICS OF NEIGHBORHOOD SPEAKING: A SOCIOPRAGMATIC STUDY - Siagian, Beslina Afriani; Sitorus, Nurhayati (Universitas Muhammadiyah Metro, 2023)
Neighboring life is a type of social interaction that shows many symptoms of social conflict. The social conflict appears in various illocutionary speech acts found in neighboring social interactions. This study examines illocutionary speech acts using listening and speaking techniques in collecting data and translational and pragmatic equivalent methods in processing data. Data was obtained naturally through mutual interaction with neighbors. This study shows variations and rich pragmatic features in neighborly interactions. All speech acts have hidden meanings that deserve to be studied. The realization of illocutionary speech acts in this study is manifested in five ways: directive speech acts of ordering, expressive speech acts of mocking, commissive speech acts of offering, assertive speech acts of boasting, and declarative speech acts of confirming. In contrast, the speaking strategy obtained from the research data is divided into four parts: speaking frankly without further ado, speaking candidly with positive Politeness, speaking candidly with negative Politeness, and the strategy of vaguely speaking. - vague. Furthermore, the factors that influence the realization of speech acts are speech situation, age, kinship, gender, social status, and social relations. This research has implications for kinship relations between neighbors. Understanding speech acts can prevent social conflict and create closeness between neighbors.